Isolation of Mesenchymal Stem Cell from Wharton’s Jelly of Human Umbilical Cord for Application in Wound Healing - Bich, Nguyen Thi; Khanh, Bui Thi Van; Huyen, Truong Linh; Thao, Chu Thi; Anh, Bui Viet; Thang, Nguyen Dinh; Liem, Nguyen Thanh; Nhung, Hoang Thi My (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Mesenchymal stem cell (MSC) is a promising source of novel cell-based therapies, driven by the hope of finding cures for numerous diseases including skin wound healing. In this study, we isolated MSCs from Wharton’s jelly of human umbilical cord by enzymatic method. To determine the effect of MSC conditioned medium on wound healing ability, we examined two MSC conditioned mediums (MSC-CM), which differ in concentration of serum and harvest time. The results showed that in serum starvation condition, MSC-CM showed significantly enhanced keratinocyte migration speed and prolonged culture of MSC in this condition also improve the efficiency of MSC-CM. Keywords: Wharton’s jelly, Mesenchymal stem cell-conditioned medium, serum starvation, wound healing.